Pathogenicity of reassortant H9 influenza viruses with different NA genes in mice and chickens. (December 2016) - Yan, Liping; Liu, Qinfang; Su, Xin; Teng, Qiaoyang; Bao, Danqi; Che, Guangsheng; Chen, Hongjun; Cui, Hongrui; Ruan, Tao; Li, Xuesong; Li, Zejun
Abstract To better understand the influence of different NA genes on pathogenicity of H9 viruses, three reassortant H9 viruses (rH9N1, H9N2 and rH9N3) were generated and characterized. All three viruses replicated efficiently in eggs and MDCK cells, whereas the rH9N1 and rH9N3 replicated more efficiently than H9N2 in A549 cells. The rH9N3 replicated more efficiently than rH9N1 and H9N2 viruses in mice, however, rH9N3 replicated and shed less efficiently than the H9N2 virus in chickens. Further studies indicate that N3 had higher NA activity and released virus from erythrocytes faster, which may improve the adaptation of H9 influenza virus to mammals.